Komparasi Kepedulian Masyarakat Desa Wargakerta Tasikmalaya dan Kelurahan Cinere Depok dalam Pembelajaran Tahsin Al-Qur’an - Rukoyah, Ade; Sa'diyah, Rika (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
This study aims to describe and analyze the forms of community concern in the learning of Qur‟anic recitation (tahsin) in two areas with different social backgrounds, namely Wargakerta Village (Tasikmalaya) and Cinere Subdistrict (Depok), focusing on an in-depth portrayal of community motivation in participating in Qur‟anic recitation (tahsin) activities. The analysis process was conducted inductively by interpreting field data to produce meaningful and contextual understanding across both research locations. This research employed a qualitative approach using a case study method. Data were collected through in- depth interviews, direct observations, and documentation, all aimed at comprehensively understanding the forms of concern and the supporting or inhibiting factors related to the motivation for learning Qur‟anic recitation (tahsin) in each area. Data analysis was carried out through data reduction, presentation, and inductive conclusion drawing. The findings reveal that the community's concern for tahsin activities remains strong in both areas, although the forms and mechanisms vary. In Wargakerta, concern is expressed through religious traditions and the involvement of local religious figures. In Cinere, it appears in more structured forms such as monthly contributions, the use of technology, and professional appreciation for tahsin instructors.